The Effect of Pseudomonas putida on the Reduction of Limonin in the De-bittering of Orange and Grapefruit Concentrates and Assessment of Physicochemical and Organoleptic Features - Yasamin Mohammadi; Peyman Rajaei; Mohammadreza Eshaghi (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2020)
The bitterness of citrus juice is one of the most important factors in the reduction of marketability in juice industry. Limonin and Narengin are known as two important compounds in bitter citrus juice during storage. Therefore, various processes, including chemical, microbial and enzymatic methods, have been used to reduce these bitter compounds. The purpose of this study was to investigate the effect of adding Pseudomonas putida bacteria on the reduction of the level of limonin and also the measurement of physicochemical and organoleptic properties. Pseudomonas putida bacteria with two concentrations of 102 and 104 cfu/mL as a causative agent of orange and grapefruit concentrate were studied. Also, the physicochemical properties of concentrates were measured at 120 h (growth time and bacterial activity). The results showed that the growth rate of bacteria had a significant effect on the reduction of lemonin, pH and turbidity levels (p < /em><0.05). Also, it has a significant effect on increasing the acidity of the treatments (p < /em><0.01). After pasteurization and inactivation of Pseudomonas putida bacteria, to ensure that bitterness is not rejected the specimens were incubated at 40 °C for 45 days and sensory characteristics were measured on days 0, 15, 30 and 45. Among the samples, T4 (orange concentrate + 104 cfu/mL) and T6 (grapefruit concentrate + 104 cfu/mL) treated with the lowest microbial growth rate in 120 h and also, in terms of general acceptance and taste, it has more points than other samples during 45 days of storage were identified as superior samples.